ChemInform Abstract: Novel α‐Tosyloxylation of Ketones Catalyzed by the in situ Generated Hypoiodous Acid from Alkyl Iodide. Issue 14 (April 2015) - Zhang, Bijun; Han, Liuquan; Hu, Jiantao; Yan, Jie
Abstract: Not only α‐tosyloxyketones, but also other α‐sulfonyloxyketones can be synthesized following this catalytic reaction.